Lack of effect of typical rapid-weight-loss practices on balance and anaerobic performance in apprentice jockeys - Cullen, S. J.; Dolan, E.; O'Brien, K.; McGoldrick, A.; Warrington, G. D. (International Journal of Sports Physiology and Performance, 2015)
Balance and anaerobic performance are key attributes related to horse-racing performance, but research on the impact of making weight for racing on these parameters remains unknown. The purpose of this study was to investigate the effects of rapid weight loss in preparation for racing on balance and anaerobic performance in a group of jockeys. Methods: Twelve apprentice male jockeys and 12 age- and gender-matched controls completed 2 trials separated by 48 h. In both trials, body mass, hydration status, balance, and anaerobic performance were assessed. Between the trials, the jockeys reduced body mass by 4% using weight-loss methods typically adopted in preparation for racing, while controls maintained body mass through typical daily dietary and physical activity habits. Results: Apprentice jockeys decreased mean body mass by 4.2% ± 0.3% (P < .001) with a subsequent increase in dehydration (P < .001). The controls maintained body mass and a euhydrated state. No differences in balance, on the left or right side, or in peak power, mean power, or fatigue index were reported between the trials in either group. Conclusion: Results from this study indicate that a 4% reduction in body mass in 48 h through the typical methods employed for racing, in association with an increase in dehydration, resulted in no impairments in balance or anaerobic performance. Further research is required to evaluate performance in a sport-specific setting and to investigate the specific physiological mechanisms involved.